2011 IEEE Nuclear Science Symposium Conference Record 2011
DOI: 10.1109/nssmic.2011.6153672
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evaluation of PET motion correction methods using MR derived motion fields

Abstract: Although there have been various proposed methods for motion correction in PET, there is not sufficient evidence to answer which method is better in terms of image quality and quantification. This study aims to characterize the behavior of the two main motion correction methods in terms of convergence and image properties. During the first method, reconstruct transform-average (RT A), independent reconstructions of each gate are transformed to a reference gate and averaged. In the second method, motion-compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…This result is consistent with previous findings that the MCIR method amplifies noise compared to the non-MoCo. [27][28][29][30][31] However, no significant difference was found between the three PET reconstructions (non-MoCo, MoCo 2000, and MoCo P2P200 ) in Dunn's post hoc pairwise comparison, perhaps due to the small sample size. Despite the higher noise levels, both MoCo 2000 and MoCo P2P200 PET images provided significantly superior lesion conspicuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous findings that the MCIR method amplifies noise compared to the non-MoCo. [27][28][29][30][31] However, no significant difference was found between the three PET reconstructions (non-MoCo, MoCo 2000, and MoCo P2P200 ) in Dunn's post hoc pairwise comparison, perhaps due to the small sample size. Despite the higher noise levels, both MoCo 2000 and MoCo P2P200 PET images provided significantly superior lesion conspicuity.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to MoCo 2000 , MoCo P2P200 has larger variations in TBR and CNR in the 5.75 mm at >90 min and 4.75 mm sphere at >70 min. This may be explained by the small size of this spheres, the low activity (<0.062 mCi at >90 min or < 0.071 mCi at >70 min) due to tracer activity decay, and the amplified noise introduced by a short MR scan duration (17 s) and MCIR PET MoCo [27][28][29][30][31]. Of note, the nominal spatial resolution of FDG PET isF I G U R E 8 Representative liver cancer patient 2.…”
mentioning
confidence: 99%
“…It has been shown by Polycarpou et al (2011) that under some circumstances MCIR may provide superior PET motion correction than RTA, but comes at greater computational cost. Our technique can also be used to provide motion estimates for MCIR-based reconstructions, and in future work we plan to investigate this.…”
Section: Discussionmentioning
confidence: 99%
“…6 For PET-MR imaging, precalibrated motion models are based on near real-time MR images acquired before the simultaneous PET-MR acquisition. This approach has been applied in MR-based PET simulation studies [24][25][26][27][28][29] with healthy volunteer MR data. 3D T1-weighted turbo field echo (TFE) MR images were acquired using parallel imaging (SENSE) with an acceleration factor of 8, so that each whole-thorax volume is acquired in 0.7 seconds.…”
Section: Respiratory Motionmentioning
confidence: 99%
“…Polycarpou and colleagues 26,27 and Tsoumpas and colleagues 29 also performed a comparison between the 2 approaches using OSEM reconstruction in an MR-based PET simulation study. They found that MCIR achieves better contrast and smaller bias in low-activity regions compared with PRR, but has lower SNR.…”
Section: Comparison Between Motion-compensated Image Reconstruction Amentioning
confidence: 99%